The Use of Wordwall in the Direct Method for Teaching Arabic Vocabulary at Manba’ul Ulum Islamic Senior High School - Muhammad Faris Setiawan; Iman Matin; Muhammad Fahri (Penerbit Minhaj Pustaka, 2026)
Mastering vocabulary is a fundamental foundation in learning Arabic. Previous research has only used Wordwall as a separate evaluation tool, without integrating it with a specific methodology and teaching method. This study aims to determine: (1) how to use Wordwall in the direct method for teaching vocabulary at SMA Manbaul Ulum and (2) its impact on vocabulary mastery. The study employed a quasi-experimental method with a pretest-posttest design for tenth-grade students on the topic